2004
DOI: 10.1002/anie.200453916
|View full text |Cite
|
Sign up to set email alerts
|

The Pristine Oil/Water Interface: Surfactant‐Free Hydroxide‐Charged Emulsions

Abstract: Stable oil‐in‐water emulsions are obtained in alkaline solution in the absence of any conventional surfactant. The oil droplets are charged by hydroxide ions (see picture). The surface charge density is obtained by measuring the size of the emulsion droplets by electroacoustics and the quantity of NaOH required to keep the pH constant during homogenization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
401
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(442 citation statements)
references
References 18 publications
38
401
2
1
Order By: Relevance
“…A similar effect was observed for oil drops in water [19,20]. The experiment showed that ζ-potential of the bubbles (drops) changes with pH from zero at pH = 2-4 up to −120 mV at pH ≈ 10.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…A similar effect was observed for oil drops in water [19,20]. The experiment showed that ζ-potential of the bubbles (drops) changes with pH from zero at pH = 2-4 up to −120 mV at pH ≈ 10.…”
Section: Introductionsupporting
confidence: 73%
“…The experiment showed that ζ-potential of the bubbles (drops) changes with pH from zero at pH = 2-4 up to −120 mV at pH ≈ 10. The surface density of charges measured for oil drops [20] corresponds roughly n s = (3 − 4) × 10 13 cm −2 at neutral pH. For bubbles in water, the charge density is expected to be in the same range, because the pH dependence of the ζ-potential is similar to that for the drops [21].…”
Section: Introductionmentioning
confidence: 88%
“…On the contrary, the second model of the e.d.l. for the oilwater and airwater interface stipulates that OH ¹ ions are preferentially adsorbed, 12 which is difficult to understand. The specific adsorption potential of the OH ¹ species requires a very high value to yield a negative surface down to a pH of 34 (i.e., at the i.e.p.)…”
Section: ç Discussionmentioning
confidence: 99%
“…For pristine emulsions can spontaneously enrich hydroxide ions at the oil/water interfaces. 29 The surfaces of the oil droplets, stabilized by hydroxide ions are therefore negatively charged and their pH are much higher than that in bulk water. By this theory, Wang and coworkers utilized the oil/water emulsions as the sacri¯cial template to prepare PDA capsules in NaOH (pH 8.2) solution, Hydroxide ions do not only stabilize the oil/water interface, but also replace TRIS bu®er to provide an alkaline circumstance for oxidation of DA.…”
Section: Soft Templatementioning
confidence: 99%